The Impact of Service Quality, Student Satisfaction, and University Reputation on Student Loyalty: A Case Study of International Students in IIUM, Malaysia - Fares, Djafri; ., Omar Kachkar (Information Management and Business Review, 2013)
The purpose of this paper is to examine the relationship between service quality, student satisfaction, university reputation, and student loyalty in the International Islamic University Malaysia (IIUM). This study aims to improve our understanding of student loyalty and to highlight the effect of student satisfaction, service quality, and brand image in building student loyalty towards IIUM. Data were randomly collected from 160 students studying in IIUM during the 2012/2013 academic session. Data analysis encompasses descriptive analysis, reliability analysis, exploratory factor analysis (EFA), correlation, and regression analysis. The data resulted in acceptably high reliability. The result indicates that all independent variables have significant impact on student loyalty. All three hypotheses were supported. This study is set to assist institutions of higher education to identify improvements in the service delivery process by identifying different aspects of service quality, brand image, and student satisfaction in IIUM.